PP.30.09: CORRELATION BETWEEN HS CRP AND N-T PRO-BNP IN PATIENTS WITH ARTERIAL HYPERTENSION (AH) AND CHRONIC RENAL FAILURE STAGE IV, BOTH WITH AND WITHOUT DIABETES MELLITUS (DM). (June 2015) - Mylonopoulou, M.; Markopoulos, P.; Mistylis, P.; Tsotras, J.; Antonopoulos, S.
Abstract : Objective: N-terminal pro-BNP (Nt proBNP) is considered one of the most important biomarkers for the prediction of major cardiovascular events and death in the general population. Our objective is to investigate the relationship between high sensitivity CRP (hsCRP) and Nt pro-BNP in hypertensive patients with chronic renal failure stage IV with or without DM. Design and method: We analyzed measurements of hsCRP and Nt pro-BNP serum levels in 25 patients with AH (group A), 25 patients with AH and type 2 DM (group B), 25 patients with AH and chronic renal failure stage IV (group C) and 25 patients with AH, chronic renal failure stage IV and type 2 DM (group D). Results: Nt pro-BNP serum levels measured in fmol/ml were found equal to 172.8 ± 47.8 in patients of group A, 976.9 ± 45 in patients of group B, 1948.4 ± 491 in patients of group C and 3143 ± 562 in patients of group D. HsCRP serum levels were found equal to 3.5 ± 0.8 mg/l, 7.5 ± 2.6, 13.5 ± 4.8, 21.5 ± 6.2 for the patients of group A, group B, group C and group D respectively. The results indicate that Nt pro-BNP levels were significantly higher in group D compared to group C (p < 0.02), group B (p < 0.0001), or group A (p < 0.00001). HsCRP levels were found significantly higher in group D compared to group B (p < 0.02) and group A (p < 0.003). In addition, a statistically significant positive correlation between hsCRP and Nt pro-BNP was detected (p < 0.001). Conclusions: According to our analysis, hypertensive patients with renal failure stage IV and DM have significantly higher serum levels of Nt pro-BNP compared to hypertensive patients without renal failure, regardless of being diabetic or not. Our essay demonstrated a significant positive correlation between Nt Pro-BNP and hsCRP, which in turn reaffirms a possibly significant pathogenetic relationship between major cardiovascular events and inflammatory response.